A Conceptual Review of Teacher Enthusiasm and Students' Success and Engagement in Chinese EFL Classes - Peng, Chunju (Frontiers in Psychology, 2021)
The swift growth and progress of colleges and universities across China noticed a request for teaching and learning English as Foreign Language (EFL), and regarding the quality of higher education, student engagement has been at the center of attention which has a remarkable role due to the arrival of positive psychology in language learning recently. To this end, on the one hand, nurturing student engagement in EFL classes corresponds to requests from the recent national university English curriculum selected in 2015 in China. On the other hand, a bulk of studies has acknowledged difficulties that hinder the construction of a learner-centric learning situation. Moreover, there is a dearth of inquires which have focused on teachers’ role in general and affective aspects namely enthusiasm, in particular. According to the literature review, the definition of these constructs, namely teacher enthusiasm and students’ success and engagement are presented. In a nutshell, the implications for teachers, university administrators, teacher-trainers, and future researchers are presented, and new directions for future research are allocated.